Pengaruh Jenis dan Konsentrasi Pemlastis terhadap Karakteristik Komposit Bioplastik Pati Ubi Talas Belitung (Xanthosoma sagittifolium) - Kitosan - Putri, Runa Ramadanty Aisyi; Hartiati, Amna; Harsojuwono, Bambang Admadi (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI; Vol 9 No 3 (2021): September, 2021)
This study aims to determine the effect of the type and concentration of plasticizers and their interactions on the characteristics of the taro potato starch bio-plastic composite and to determine the type and concentration of the plasticizer that produces the best characteristic of the taro starch bio-plastic composite. This study used a factorial randomized block design. The first factor is the type of plasticizer which consists of 4 levels, namely glycerol, sorbitol, castor oil, and stearic acid. The second factor is the concentration of plasticizers with 4 levels, namely 0.5%; 1%; 1.5%; 2%. Each treatment was grouped into 2 based on the time of making bio-plastics, so there were 32 experimental units. The variables observed were tensile strength, elongation at break, elasticity, thickness expansion, water vapor transmission rate, and biodegradation. The data obtained were analyzed for diversity and continued with the Honest Significant Difference test. The results showed that the type and concentration of plasticizers and their interactions had a very significant effect on tensile strength, elasticity, thickness expansion and water vapor transmission rate. The type of plasticizer and the concentration of the plasticizer have a very significant effect, while the interaction has no significant effect on elongation at break. The type of plasticizer and the concentration of the plasticizer and their interactions have no significant effect on biodegradation. The best characteristics of bio-plastic composites occurred when using stearic acid plasticizer with a concentration of 0.5% with a tensile strength value of 23.00 MPa, elongation at break 2.22%, elasticity 1038.27 MPa, expansion 91.47%, water vapor transmission rate 1.38 g/m2.hour and 7 days of degradation. The bioplastics produced in this study have met the standards of SNI 7818:2014 on the variable tensile strength, elasticity and international standards ASTM 5336 on the variable length of degradation. Key words: taro tuber starch, chitosan, composites bio-plastic, type and concentration of plasticizer.